Acquired Acrodermatitis Enteropathica in a 28-Year-Old Male with Type 1 Diabetes - Owen Ngalamika; Wencilaus M. P. Selvaraj; Fatima K. Yikona; Chibamba Mumba (Hindawi Limited, 2021)
Acrodermatitis enteropathica (AE) is a rare disorder arising from inherited or acquired zinc deficiency. It is mainly characterized by acral dermatitis, periorificial dermatitis, alopecia, and gastrointestinal symptoms in the form of diarrhea. There are many complications of AE including local and systemic infections that may develop as a result of untreated AE. In addition, due to the role of zinc in glucose metabolism, chronic zinc deficiency may pose a challenge in the control of blood glucose levels in diabetics. We report the case of a 28-year-old male with type 1 diabetes who presented with signs and symptoms of AE.